Exploring the Nexus: Benchmarking and Educational Institution Performance - Khoirinindyah, Safitri; Rindaningsih, Ida (JURNAL AL-TANZIM, 2023)
Whether an educational institution develops or not depends on its performance. To improve this performance, many things are done, including how leaders help improve institutional performance in developing competitiveness, one of which is through benchmarking. From this, researchers want to know whether there is a relationship between benchmarking and institutional performance. This research aims to determine the relationship between benchmarking and performance at one State Madrasah Aliyah in East Java. The research method used in this research is a quantitative approach. The data collection method uses a Likert scale. The population and sample use a saturated sample technique or a total sample with 35 respondents. The data analysis technique uses Product Moment correlation. This research shows a relationship between benchmarking and institutional performance with evidence of a product-moment correlation value of 0.430 with a significance value of 0.010 (p < 0.05), which means that Ha is accepted and Ho is rejected. This research provides implications for benchmarking and institutional performance in competitiveness development.